ΔKi67 proliferation index as independent predictive and prognostic factor of outcome in luminal breast cancer: data from neoadjuvant letrozole-based treatment - A Ianza; F Giudici; C Pinello; SP Corona; C Strina; O Bernocchi; M Bortul; M Milani; M Sirico; G Allevi; S Aguggini; A Cocconi; et al. (Tumor Biology)
A key tool for monitoring breast cancer patients under neoadjuvant treatment is the identification of reliable predictive markers. Ki67 has been identified as a prognostic and predictive marker in ER-positive breast cancer. Ninety ER-positive, HER2 negative locally advanced breast cancer patients received letrozole (2.5 mg daily) and cyclophosphamide (50 mg daily) with/without Sorafenib (400 mg/bid daily) for 6 months before undergoing surgery. Ki67 expression and tumor size measured with caliber were determined at baseline, after 30 days of treatment and at the end of treatment. Patients were assigned to a clinical response category according to Response Evaluation Criteria in Solid Tumors, both at 30 days and before surgery and further classified as high-responder and low-responder according to the median variation of Ki67 values between biopsy and 30 days and between biopsy and surgery time. The predictive role of Ki67 and its changes with regard to clinical response and survival was analyzed. No differences in terms of survival outcomes emerged between the arms of treatment, while we observed a higher percentage of women with progression or stable disease in arm with the combination containing Sorafenib (20.5% vs 7.1%, p = 0.06). Clinical complete responders experienced a greater overall variation in Ki67 when compared with partial responders and patients with progressive/stable disease (66.7% vs 30.7%, p = 0.009). High responders showed a better outcome than low responders in terms of both disease-free survival ( p = 0.009) and overall survival ( p = 0.002). ΔKi67 score evaluated between basal and residual tumor at definitive surgery showed to be highly predictive of clinical complete response, and a potential parameter to be used for predicting disease-free survival and overall survival in luminal breast cancer treated with neoadjuvant endocrine-based therapy.